On the periodic orbits and the integrability of the regularized Hill lunar problem - Llibre, Jaume; Roberto, Luci Any [UNESP] (American Institute of Physics (AIP), 2011)
The classical Hill's problem is a simplified version of the restricted three-body problem where the distance of the two massive bodies (say, primary for the largest one and secondary for the smallest one) is made infinity through the use of Hill's variables. The Levi-Civita regularization takes the Hamiltonian of the Hill lunar problem into the form of two uncoupled harmonic oscillators perturbed by the Coriolis force and the Sun action, polynomials of degree 4 and 6, respectively. In this paper, we study periodic orbits of the planar Hill problem using the averaging theory. Moreover, we provide information about the C-1 integrability or non-integrability of the regularized Hill lunar problem. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3618280]